2006
DOI: 10.1124/jpet.106.107599
|View full text |Cite
|
Sign up to set email alerts
|

The New Low Calcemic Vitamin D Analog 22-Ene-25-Oxa-Vitamin D Prominently Ameliorates T Helper Cell Type 1-Mediated Colitis in Mice

Abstract: In addition to its well defined role as a key regulator of calcium and bone metabolism, 1,25-dihydroxyvitamin D 3 (calcitriol) has been established as a potent modulator of immune cell function. Still, because of the hypercalcemic toxicity occurring after systemic application of the parent compound, its clinical application as an immunosuppressant has been hampered. Recently, we described 22-ene-25-oxa-vitamin D (ZK156979) as a representative of a novel class of low calcemic vitamin D analogs with well preserv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 41 publications
3
33
0
Order By: Relevance
“…This is contrary to previous observations in NOD mice with autoimmune prostatitis, where chronic administration of a VDR agonist (elocalcitol) at 100 g/kg/day for 10 -16 days reduced the capacity of lymph node-derived CD4 ϩ T cells to secrete IFN-␥ upon further stimulation in vitro (24). Furthermore, reduced IFN-␥ and increased IL-4 levels were detected in colon protein extracts from mice treated with 0.2 g of calcitriol/kg/day for 3 days in a model of Th1-mediated colitis (23). In these previous studies, mice were chronically administered significantly greater doses of 1,25(OH) 2 D 3 or a VDR agonist than used in the current experiments.…”
Section: Topical 125(oh) 2 D 3 Did Not Alter the Phenotype Or Cellulmentioning
confidence: 87%
See 2 more Smart Citations
“…This is contrary to previous observations in NOD mice with autoimmune prostatitis, where chronic administration of a VDR agonist (elocalcitol) at 100 g/kg/day for 10 -16 days reduced the capacity of lymph node-derived CD4 ϩ T cells to secrete IFN-␥ upon further stimulation in vitro (24). Furthermore, reduced IFN-␥ and increased IL-4 levels were detected in colon protein extracts from mice treated with 0.2 g of calcitriol/kg/day for 3 days in a model of Th1-mediated colitis (23). In these previous studies, mice were chronically administered significantly greater doses of 1,25(OH) 2 D 3 or a VDR agonist than used in the current experiments.…”
Section: Topical 125(oh) 2 D 3 Did Not Alter the Phenotype Or Cellulmentioning
confidence: 87%
“…The greatest reductions in proliferation were observed at 4 and 7 days post 1,25(OH) 2 D 3 administration (Fig. 2D) [22][23][24]. To determine whether this occurred in our model, cytokine levels were examined in culture supernatants obtained 92 h after the coculture of APC with CD4 ϩ cells from the SDLN of treated mice.…”
Section: Cd4 ϩ Cells From 125(oh) 2 D 3 -Treated Mice Had Reduced Camentioning
confidence: 99%
See 1 more Smart Citation
“…For example, culturing dendritic cells (DCs) with the active form of vitamin D, 1α,25-dihydroxyvitamin D3 (1α25VitD3) leads to impaired DC maturation, development of tolerogenic properties [3], and the capacity to induce CD4 + Foxp3 + cells with suppressive activity [4], or IL-10 expressing Treg cells [5]. In animal models of human disease, administration of 1α25VitD3 successfully treats transplant rejection [6] and a range of autoimmune conditions, including antiretinal autoimmunity [7], acute colitis [8], diabetes [6], arthritis [9], and EAE [10], as well as allergic airway disease [11]. These studies demonstrate a correlation between therapeutic efficacy and increased frequency or quantities of CD4 + CD25 + T cells, IL-10, TGF-β, and CTLA-4.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, vitamin D deficiency has been shown to accelerate the development of IBD symptoms among IL-10 knockout mice that develop spontaneous enterocolitis [7] . Also, calcitriol treatment reduces the ability of IL-10 knockout mice to produce and to respond to www.wjgnet.com TNF-α [8] , and it has recently been shown that application of a calcitriol analog reduces intestinal inflammation in a 2,4,6-trinitrobenzene sulfonic acid colitis model [9] . Calcitriol is the activated form of vitamin D3 that binds to a nuclear receptor protein.…”
Section: Introductionmentioning
confidence: 99%